Loss Leading as an Exploitative Practice - Chen, Zhijun; Rey, Patrick (American Economic Review, 2012)
We show that large retailers, competing with smaller stores that carry a narrower range, can exercise market power by pricing below cost some of the products also offered by the smaller rivals, in order to discriminate multistop shoppers from one-stop shoppers. Loss leading thus appears as an exploitative device rather than as an exclusionary instrument, although it hurts the smaller rivals as well; banning below-cost pricing increases consumer surplus, rivals' profits, and social welfare. Our insights extend to industries where established firms compete with entrants offering fewer products. They also apply to complementary products such as platforms and applications. (JEL L11, L13, L81)